Original research - couple's sexual dysfunctions: sexual disorders in infertile couples - Wischmann, Tewes (The journal of sexual medicine, 2010)
Introduction - Sexuality and the desire for a child are strongly interconnected. The same applies to sexual disorders and the unfulfilled desire for a child. - Aim - This article indicates the relations between sexual disorders and the unfulfilled desire for a child and outlines the potential effects of diagnostics and treatment in the context of reproductive medicine on the couples' sexuality. - Methods - A research drive was undertaken in well-established medical and psychological literature database with the keywords “infertile” or “infertility” and “sexual dysfunction” or “sexual satisfaction.” - Results - Sexual dysfunctions (of organic or of psychic origin) as a cause of involuntary childlessness are relatively unusual. By contrast (temporary) sexual disorders resulting from diagnosis and medical therapy are common in couples with fertility problems, with women more frequently affected than men. - Conclusions - Counseling for couples with the unfulfilled desire for a child should invariably include explicit and appropriately tactful reference to sexuality and (functional) sexual disorders by the therapist. Wischmann TH. Sexual disorders in infertile couples.
Gesehen am 15.03.2024